Egyptian-Hungarian diplomatic relations between World War I. and II. - Abdel-Aty, Abdallah (Études sur la Région Méditerranéenne, 2011)
Egypt and Hungary have a long common historical past, which is characterized by fruitful diplomatic and political cooperation. The twenty years between 1919 and 1939 included a significant, active, and changeable period in the history of diplomatic and political relation between Hungary and Egypt according to the archive material, other sources and articles of the Egyptian press. The chronological frame of this research has a precise starting-, and end-point. The plan of the establishment of a Hungarian Consulate in Cairo on 10 January 1924 can be regarded as the beginning. The final event was on 30 April 1939 when Miklós Horthy, the son of the regent of Hungary, visited Egypt again to negotiate and discuss with Egyptian officials. The period between 1919 and 1939 has been studied on the basis of the sources of the archive of the Egyptian Foreign Ministry and the contemporary Arabic, English and French press in Egypt.